Analisis Pola Komunikasi dengan Chatgpt dalam Perspektif Psikologis pada Mahasiswa Universitas Pendidikan Indonesia - Zahra Hasna Nabilla; Restu Arsyana; Hanum Nur Alifia; Misbah Abdul Aziz; Firman Aziz; Ryan Ferdiana (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
In the digital era, students' interactions with technology have become increasingly widespread, including the use of artificial intelligence such as ChatGPT as a medium for both academic and personal communication. This study aims to analyze the communication patterns between students of Universitas Pendidikan Indonesia and ChatGPT, as well as its psychological impacts on users. This research employs a descriptive qualitative method, using in-depth interviews with three students from Universitas Pendidikan Indonesia and documentation in the form of conversation transcripts. The findings reveal that students utilize ChatGPT as a source of academic information, a discussion partner, and a tool for personal reflection. The communication patterns observed exhibit supportive, responsive, and affective styles. Psychologically, interacting with ChatGPT provides a sense of comfort, boosts self-confidence, and helps reduce academic anxiety. However, there is also a potential risk of dependency on the instant responses provided by artificial intelligence. This study recommends the development of digital communication literacy and the conscious use of technology to ensure that human–AI interactions remain psychologically healthy and productive.